EFFECTIVE THERAPEUTIC INTERVENTIONS TO PROMOTE RECOVERY FROM FIRST PSYCHOTIC EPISODE AND MINIMIZE ITS RELAPSE: A QUALITATIVE STUDY FROM PAKISTAN: First Psychotic Episode - Khalil, Rehana; Naeem, Zahid; Jameel, Nazia; Talib, Uroosa (Pakistan Armed Forces Medical Journal, 2021)
Objective: To explore effective therapeutic strategies to promote recovery from first episode of psychosis and minimize its relapse.Study Design: Qualitative study.Place and Duration of Study: Karwan-e-Hayat Psychiatric Care and Rehabilitation Center, Karachi, from Mar to Jun 2019.Methodology: Seventeen participants were recruited through purposive sampling and data was collected through in-depth interviews. Qualitative thematic content analysis was done through generation of a coding scheme.Results: Almost half i.e., 8 (47%) had experience of 10 years, while 7 (41%) had 15 years’ experience, and 2 (12%) had 30 years’ experience as psychiatrists. Analysis of the interview transcripts revealed three main themes related to psychiatrists’ views on interventions for first episode of psychosis to prevent relapse: (1) duration of first episode of psychosis (2) compliance and rate of recovery after first episode (3) effective interventions for first episode psychosis.Conclusion: The effective interventions to promote recovery from first psychosis episode and minimize its relapse included multiple combinations of integrated stage-specific approaches necessitating antipsychotics (pharmacological) and psychosocial support (non-pharmacological).